The absence of future: a look at the historical consciousness of history students in Mexico (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
This article analyzes the results of two doctoral research projects that explore historical consciousness among university students in Mexico. Specifically, it seeks to understand history undergraduate students and their relationship with the future. The first study was carried out with young people from the Universidad Nacional Autónoma de México (UNAM) in the country's capital based on Jörn Rüsen's perspective, and the second, with students from the Universidad Autónoma de Chihuahua (UACH), in Chihuahua City, using Grounded Theory as the methodological approach. Among their main results, both studies identify three general trends: the future as the temporal dimension that receives the least attention; the prominence of the present to build an argument with a prospective view; and a pessimistic collective vision about the future.
Keywords: teaching & learning history; historical consciousness; future; students